2018
DOI: 10.3389/fcimb.2018.00055
|View full text |Cite|
|
Sign up to set email alerts
|

gga-miR-155 Enhances Type I Interferon Expression and Suppresses Infectious Burse Disease Virus Replication via Targeting SOCS1 and TANK

Abstract: Infectious bursal disease (IBD) is an acute, highly contagious, and immunosuppressive avian disease caused by IBD virus (IBDV). MicroRNAs (miRNAs) are involved in host-pathogen interactions and innate immune response to viral infection. However, the role of miRNAs in host response to IBDV infection is not clear. We report here that gga-miR-155 acts as an anti-virus host factor inhibiting IBDV replication. We found that transfection of DF-1 cells with gga-miR-155 suppressed IBDV replication, while blockage of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 70 publications
(99 reference statements)
0
42
0
Order By: Relevance
“…Recently, an increasing number of lncRNAs have been reported to play roles in innate immune response to virus infections (Ma et al, 2016;Ouyang et al, 2016). Previous studies have implicated miR-155 in host immunity against viral infections and regulation of type I IFN signalling (Harrison et al, 2017;Thounaojam et al, 2014;Wang et al, 2018;Wang, Hou, et al, 2010;Zhou et al, 2010). In this study, both in vitro and in vivo experiments demonstrated that altering lncRNA-155 expression had a profound effect on host antiviral response and IAV replication.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…Recently, an increasing number of lncRNAs have been reported to play roles in innate immune response to virus infections (Ma et al, 2016;Ouyang et al, 2016). Previous studies have implicated miR-155 in host immunity against viral infections and regulation of type I IFN signalling (Harrison et al, 2017;Thounaojam et al, 2014;Wang et al, 2018;Wang, Hou, et al, 2010;Zhou et al, 2010). In this study, both in vitro and in vivo experiments demonstrated that altering lncRNA-155 expression had a profound effect on host antiviral response and IAV replication.…”
Section: Discussionmentioning
confidence: 59%
“…and S5a). miR-155 is thought to inhibit the expression of some negative regulators of type I interferon signalling (Thounaojam et al, 2014;Wang et al, 2018;Wang, Hou, et al, 2010); thus, we asked whether lncRNA-155 might also promote the antiviral immune response by inhibiting negative regulator(s) of type I IFN signalling.…”
Section: Ectopic Expression Of Lncrna-155 Promotes Type I Ifn Produmentioning
confidence: 99%
See 2 more Smart Citations
“…Many research results have reported that some miRNAs are involved in viral life cycles by regulating the innate immune response. For example, miR-146a facilitates replication of dengue virus by dampening interferon induction by targeting TRAF6 [45], and miR-155 enhances type I interferon expression to suppress infectious burse disease virus (IBDV) replication via targeting negative regulators, SOCS1 and TANK [46]. Additionally, miRNAs can regulate downstream IFN-I-induced signalling.…”
Section: Discussionmentioning
confidence: 99%